2012
DOI: 10.4274/jcrpe.851
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism in children: natural history and when to treat

Abstract: Subclinical hypothyroidism (SH) is a quite common disorder in the pediatric age group. The aim of this paper is to present a review of the studies investigating the natural course of SH and the effects of replacement therapy with levothyroxine in childhood. We systematically searched PubMed, Cochrane, and EMBASE (1990 to 2012) and identified 14 articles suitable to be included. SH is a benign process that does not influence anthropometric parameters or puberty onset, and in most cases, it is a remitting diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 37 publications
3
35
2
9
Order By: Relevance
“…16 On the other hand, it is well known that SH may have a different outcome in idiopathic cases [21][22][23][24][25] and in those with an underlying HT. [26][27][28][29] It has clearly been shown that in children without HT or other thyroid diseases, DS may be associated with higher TSH levels, probably due to an inherent TSH setting disorder which seems to be peculiar to DS. 30 On the basis of such findings, these authors concluded that diagnosis of SH might be overestimated in DS and that L-T4 therapy in these patients should be contemplated only when TSH values are HT diagnosis due to the initial finding of a transient hyperthyroid biochemical picture, but at that time they had been negative.…”
Section: Resultsmentioning
confidence: 99%
“…16 On the other hand, it is well known that SH may have a different outcome in idiopathic cases [21][22][23][24][25] and in those with an underlying HT. [26][27][28][29] It has clearly been shown that in children without HT or other thyroid diseases, DS may be associated with higher TSH levels, probably due to an inherent TSH setting disorder which seems to be peculiar to DS. 30 On the basis of such findings, these authors concluded that diagnosis of SH might be overestimated in DS and that L-T4 therapy in these patients should be contemplated only when TSH values are HT diagnosis due to the initial finding of a transient hyperthyroid biochemical picture, but at that time they had been negative.…”
Section: Resultsmentioning
confidence: 99%
“…In childhood, this is an even more controversial issue (6,7,8,9,10) and the only available study comparing the effects of L-T 4 treatment vs no therapy in idiopathic SH suggests that therapy is unable to modify post-therapy outcome of hyperthyrotropinemia and to prevent the risks of a subsequent TSH increase after treatment withdrawal (11). In the children with HT-related mild SH, it has been just recently reported that the evolution of thyroid function tests seems to be frequently characterized by a deterioration over time, whereas such risk is very low in the children with idiopathic SH (12).…”
Section: Introductionmentioning
confidence: 99%
“…The decision about the treatment of SH in pediatric patients is still a matter of debate. None of the consensus statements published about the management of SH addressed the issue of SH in the pediatric population [6]. …”
Section: Introductionmentioning
confidence: 99%